Adjustment of Irrigation Regime for the Agricultural Crops through CROPWAT Software Application - Avetyan, N. E. (ՀԱԱՀ հիմնադրամ)
The efficient management of the irrigation water is of utmost importance in conditions of the irrigated agriculture; hence, new methods are currently being developed and new devices are applied to achieve the maximum savings in water consumption. The computation method introduced in the current article is the best option for the identification of efficient water consumption standards, which will entail to appropriate management and savings in irrigation water. The abovementioned method has been applied in the other regions of Armenia as well, where the best indicators for irrigation water consumption have been also recorded.
Keywords: Agricultural Engineering